The influence of jargon in lexical borrowing from English (Philologia, 2021)
In all natural languages, lexical borrowing is an inevitable process in the growth of the vocabulary. The English language having established its dominance and having assumed the position of the giving language in contact with other languages, the paper examines the impact English makes on Serbian vocabulary, in the ﬁeld of jargon used by professional and subcultural groups. The analysis of written corpora within specialized areas of interest, e.g. electronics and ﬁlm industry, points to numerous loan terms in the Serbian language. The models of loans belong to well-deﬁned systems of specialized terminology in English, but the loans have not been completely adapted in their form. The instances of adaptation by translation are minor, while morphological adaptation is primarily unsystematic. From the sociological point of view, the corpus of terms borrowed from English reveals industrial and cultural inﬂuence of the English-speaking community over professional and subcultural groups of a dissimilar language